ABSORPTION AT X-RAY DIFFRACTION BY THE ONE-DIMENSIONAL SUPERLATTICE WITH A STACKING FAULT - Manukyan, H.M.; Manukyan, S.M. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
The problem is considered of a dynamic reflection of a plane monochromatic X-ray wave at the superlattice with a stacking fault between the layers when absorption is taken into account. It is shown, that taking absorption into account reduces the reflectivity in the direction of satellites. At the same time, the closer stacking fault is to the crystalline surface, the less impact it has on the reflectivity.
Keywords: X-ray diffraction, superlattice, defects